Sectarian Intolerance in Pakistan: An Analysis of Causes, Challenges, and Solutions - Suhaib, Abdul Quddus; Aziz, Farhat (Islamic Studies, 2023)
Islam provides a complete code of life. It respects the rights of the individual and balances them with the duties that one owes to society. As a result, Islam not only recognizes differing opinions but also gives them due respect. However, there are Muslims who deny this right, marking a critical point where religious extremism begins. Today Muslims are divided into many groups and sects. Instead of expressing joy and unity with their co-religionists under the spirit of the Ummah, some Muslims are bent on destroying their brothers through sectarianism. This problem has become particularly relevant in the case of contemporary Pakistan, where sectarianism has become a poison that threatens national unity. This analytical write-up discusses the reasons for sectarianism in Pakistan and outlines the external and internal elements that have influenced it. It also provides several suggestions and policy recommendations that will help prevent sectarianism.